Note su alcune interpretazioni dello stato attuale degli studi della mitologia slava Pripombe k nekaterim interpretacijam današnjega stanja raziskav slovanske mitologije - Mikhailov, Nikolai (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article is dedicated to the Mediterranean Ethnological Summer School (MESS) anthology that was edited by Bojan Baskar and Irena Weber and published in Ljubljana in 2002. The publication contains a discussion on several conclusions suggested by L. Moszyński in his article Between Fantasy and Scholarship: On Alleged Early Slavic Deities. Certain doubts have arisen concerning his attempt at Celtic interpretations of certain Slavic theonyms (Prove, Veles). It is also somewhat surprising that Moszyński has not taken into account some of the most recent research works on the reconstruction of Slavic paganism (on the reconstruction of the »principal myth« based on Slovene tradition, on the latest works on Daž’bog, and others) as well as the data from Baltic mythology. This article in an invitation to all Slavicists presently engaged in the research of mythological themes to take part in a constructive discussion and contribute their views on the subject.